Design and development of single seater electric sccoter for short distance application - Abdul Hafiz, Ramli (2008)
This project is to design and develop of single seater electric scooter. It is rear wheel drive and operates by DC motor which takes energy from dual rechargeable batteries. The conceptual design of this model is comes from mantis behaviors which fold its hand to eat. From that, the conceptual design of this scooter makes to be foldable. Rear arm and handle bar recognize to be fold due to component attach on it Dimension of the scooter model comes from real human model. Handle height, seat and foot rest location is based on Malaysian normal human size. By using 3D software, the part of model started to sketch. Part by part create before assemble together to see the model how comes out. Modification on part done to makes it join perfectly. The strain stress of model then is analyzed by using CAE software. Modification by attach support is to make structure more strong at critical point. In materials using, mild steel is choose as a main structure and joining by welded. It covers by aluminum from 6000 series with 2.5mm thickness. These materials also for rear arm main structure. Rivet at certain part is use to join this materials to steel plate and main structure. Component of model attach by bolt and nat. For the transmission, it use gearing to change rotational of DC motor. Power from that then transfer to rear wheel by sprocket and chain. From technical drawing and conceptual design, component of model being fabricate using FKM laboratory tools. Part by part create then be fabricate together. Several parts being in refinement process to make sure it can be joining very well. At the end of the project, the model tested by several person and their comment then being record. This model can work properly after all work done.